2010
DOI: 10.1111/j.1523-5378.2010.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Potential Risk Factors for Helicobacter pylori Infection in Brazilian Children

Abstract: Background:Helicobacter pylori infection has been proved to be of great relevance to public health in unindustrialized countries, especially in low socioeconomic groups. Poor hygiene, deficient sanitation, and crowded conditions have been reported as risk factors for this infection. In this work, we investigated whether social and demographic characteristics were associated with anti-H. pylori IgG antibodies in 1104 children aged 4–11 years old from Salvador, a large city located in northeastern Brazil.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
3
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 36 publications
(35 reference statements)
6
62
3
6
Order By: Relevance
“…The primary risk factors for acquiring H pylori in Brazil are related to unfavorable living conditions experienced during childhood, including low family income, low education levels of the children's parents, lack of proper household sanitary facilities, household crowding or high density housing or in institutions; improper personal hygiene habits, presence of an infected family member, especially the mother, and deficient basic public health services such as supply of piped drinking water, household garbage collection and sewerage with treatment plants for collected waste (9,36,55,56,79,110) .…”
Section: Group 5 Epidemiology Of Infection and Proposals For Action mentioning
confidence: 99%
“…The primary risk factors for acquiring H pylori in Brazil are related to unfavorable living conditions experienced during childhood, including low family income, low education levels of the children's parents, lack of proper household sanitary facilities, household crowding or high density housing or in institutions; improper personal hygiene habits, presence of an infected family member, especially the mother, and deficient basic public health services such as supply of piped drinking water, household garbage collection and sewerage with treatment plants for collected waste (9,36,55,56,79,110) .…”
Section: Group 5 Epidemiology Of Infection and Proposals For Action mentioning
confidence: 99%
“…85 A study, with Brazilian children, showed that the number of siblings and nursery attendance were positively associated with H. pylori infection and also that the house location (served by paved road or not) is a potential risk factor for infection, indicating that contaminated soil may be a source of infection, and concluding that the H. pylori infection in children is highly related to poor hygiene and crowded conditions. 86 A study conducted in six Latin-American countries also reported that crowding was positively associated with H.…”
Section: 7879mentioning
confidence: 99%
“…Researchers have also found that infection with H. pylori can result in cardiovascular, hematological, hepatobiliary, and metabolic diseases (5)(6)(7)(8)(9). Currently, many epidemiological surveys have been performed to identify risk factors for H. pylori infection; age, obesity, and type 2 diabetes mellitus have been identified as risk factors (10)(11)(12)(13). In terms of diagnosis, stool antigen testing, gastric biopsies, CLO-test, and urea breath test are used.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of diagnosis, stool antigen testing, gastric biopsies, CLO-test, and urea breath test are used. However, 13 C-urea breath test is the best known and most widely used test for detecting the presence of H. pylori infection and showed excellent accuracy compared to histology (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation